Association Between Soil Transmitted Helminth Infections, Hemoglobin Levels, and Eosinophil Counts in Elementary School Children - Shella Nur Laily; Retno Sasongkowati; Evy Diah Woelansari; Museyaroh (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Soil-Transmitted Helminths (STH) remain a major public health concern among school-aged children, particularly in regions with limited sanitation and inadequate hygiene practices, where chronic parasitic exposure may impair hematological health. This study investigates the extent to which STH infection is associated with reduced hemoglobin levels and elevated eosinophil counts in elementary school children, focusing on the potential hematological and immunological consequences of infection. A cross-sectional analytical design was applied to 44 participants selected by consecutive sampling. Fecal samples were examined using the 33% zinc sulfate (ZnSO₄) flotation method to detect helminth eggs or larvae, while venous blood samples from infected participants were analyzed with an automated hematology analyzer to obtain hemoglobin concentration and eosinophil percentages. Normality testing was conducted using the Shapiro–Wilk test, and associations between variables were assessed using Spearman’s rho correlation. The findings indicate that 10 of the 44 children (22.7%) were positive for STH infection. Among these infected subjects, 70% exhibited hemoglobin levels below the normal threshold, while 60% showed eosinophil counts exceeding the reference range. Statistical analysis demonstrated a significant negative correlation between STH infection and hemoglobin levels (p = 0.040), and a significant positive correlation between STH infection and eosinophil counts (p = 0.037). These results indicate that STH infections contribute to anemia and eosinophilia, suggesting measurable disruption of hematological function. The study concludes that implementing routine deworming, blood screening, and hygiene-centered health education within school-based programs is essential to reduce STH prevalence and safeguard children’s physiological well-being and cognitive development in endemic areas.